DETERMINING THE DEGREE OF ADAPTABILITY OF MODERN LABOR COST TO INNOVATIVE CONSTRUCTIVE AND TECHNOLOGICAL SOLUTIONS OF FRAME CONSTRUCTION - Рашківський, Володимир; Шандра, Олена (SWorldJournal, 2025)
The article considers the problem of determining labor standards in accordance with the application of modern structural and technological solutions of frame construction. The problems of applying the current labor standards of construction processes in